SUSTAINABILITY OF OSING TRIBE FARMING IN KEMIREN VILLAGE, BANYUWANGI - Parmawati, Rita; Yanti, Indah; Gunawan, Fahdynia Karnira; Rahmawati, Nadhea Oktaviantina; Ashari, Fadhil Muhamad (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Sustainable agricultural development offers benefits and environmental concerns, but challenges arise in land conversion processes in today's age. Kemiren Village, also known as Osing Village, is where most people are farmers. Rice production and farmers' income are decreasing yearly due to several factors that cause the importance of sustainable development planning. Based on these problems, this study aims to analyze the index and sustainability status of farming in Kemiran Village, Glagah District, Banyuwangi. This research instrument was carried out using observation, structured interviews, and distributed questionnaires, and it was analyzed by multi-dimensional scaling (MDS). The reliability test confirms all dimensions are reliable for sustainable status testing, the availability of rice pest predators influenced the ecological sustainability index value, the certification of rice seeds used, and the application of pesticides following recommendations. The economic sustainability index had savings, adequate farming equipment, and infrastructure facilities in the agricultural sector. Savings, adequate farming equipment, and adequate infrastructure facilities in the agricultural sector influenced the economic sustainability index. The sustainability status of sustainable agriculture needs to be considered with each dimension: ecological dimension 33.51, economic dimension 32.00, and social dimension 40.00 so that it is categorized as less sustainable because it is in the range of 25.01 - 50.00. MDS analysis shows that the error factor in each attribute was relatively small, in the differences in each respondent's assessment of the attributes studied, errors in entering data, and missing data.